Pendidikan Kesehatan Menggunakan Video Animasi offline dan Online Berpengaruh terhadap Pengetahuan Keluarga Tentang Pencegahan Dini Penyakit TBC - Alwan Wijaya; Sukardin; Patria Izawati; Ageng Abdi Putra (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Intoduction: Tuberculosis (TB) remains a significant global health challenge. In 2020, approximately 9.9 million people worldwide were affected by this disease. Specifically in West Lombok (Lobar), based on data from the West Nusa Tenggara Provincial Health Office, there were 2,513 cases of TB, with the highest prevalence observed in the Gunungsari area of West Lombok.Purpose: The aim of this study was to compare the impact of health education using offline and online animated videos on family knowledge regarding early prevention of TB in the working area of the Gunungsari Community Health Center in West Lombok.                                                                                           Method: The study population consisted of families of TB patients, totaling 56 respondents. Using purposive sampling, a sample of 40 respondents was divided into two groups. The research instrument included a questionnaire, and paired sample t-tests were conducted for analysisResult: The results revealed that before the intervention, with statistically significant results (p < α, where α = (0,01< 0.05).                                                                                                                                     Conclusion: In conclusion, the study found that there is a difference in the impact of health education using offline and online animated videos on family knowledge regarding early prevention of TB in the Gunungsari area of West Lombok